2020
DOI: 10.23846/tw14ie120
|View full text |Cite
|
Sign up to set email alerts
|

Promoting latrine use in rural Karnataka using the risks, attitudes, norms, abilities and self-regulation (RANAS) approach

Abstract: About 3ieThe International Initiative for Impact Evaluation (3ie) promotes evidence-informed, equitable, inclusive and sustainable development. We support the generation and effective use of high-quality evidence to inform decision-making and improve the lives of people living in poverty in low-and middle-income countries. We provide guidance and support to produce, synthesise and quality-assure evidence of what works, for whom, how, why and at what cost.3ie impact evaluations 3ie-supported impact evaluations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 24 publications
1
4
0
Order By: Relevance
“…The Swachh Bharat Mission is likely responsible for the increase in self-reported latrine use in control areas, but the increase in the intervention arms that was beyond that observed in the control arms can be attributed to the evaluated interventions. This finding is consistent with the results the individual studies reported in their independent analyses, which indicated positive effects on latrine use in Karnataka, Odisha, and Gujarat, with null effects in Bihar (Caruso et al, 2019b;Chuahan et al, 2019;Friedrich et al, 2019;International Initiative for Impact Evaluation, 2020;Schmidt, Wolf-peter, Chauhan et al, 2020;Viswanathan et al, 2019). However, the calculation of the average effect across all four studies has the added benefit of being both statistically more powerful and applicable to a broader set of contexts.…”
Section: Discussionsupporting
confidence: 86%
See 3 more Smart Citations
“…The Swachh Bharat Mission is likely responsible for the increase in self-reported latrine use in control areas, but the increase in the intervention arms that was beyond that observed in the control arms can be attributed to the evaluated interventions. This finding is consistent with the results the individual studies reported in their independent analyses, which indicated positive effects on latrine use in Karnataka, Odisha, and Gujarat, with null effects in Bihar (Caruso et al, 2019b;Chuahan et al, 2019;Friedrich et al, 2019;International Initiative for Impact Evaluation, 2020;Schmidt, Wolf-peter, Chauhan et al, 2020;Viswanathan et al, 2019). However, the calculation of the average effect across all four studies has the added benefit of being both statistically more powerful and applicable to a broader set of contexts.…”
Section: Discussionsupporting
confidence: 86%
“…This study builds on the work of the four independent impact (Caruso et al, 2019b;Chuahan et al, 2019;Friedrich et al, 2019;International Initiative for Impact Evaluation, 2020;Schmidt, Wolf-peter, Chauhan et al, 2020;Viswanathan et al, 2019). By using a common analytical approach to synthesize findings across studies, we are able to identify similarities in predictors of latrine use, such as sex and caste, and differences in predictors of latrine use, such as age, across these four states.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Only the intervention in Karnataka aimed to increase safe disposal of child faeces, and found no effect. 33 Collectively, these studies show the challenge of achieving the changes in sanitation practices that are necessary to prevent faecal exposures and improve health.…”
Section: Resultsmentioning
confidence: 99%